Influence of geomagnetic disturbances on myocardial infarctions in women and men from Brazil - Luiz Felipe C. Rezende; Eurico R. De Paula; Marcio T. A. H. Muella; Severino L. G. Dutra; Reinaldo R. Rosa; Paulo H. N. Saldiva; Jean P. H. B. Ometto (Communications Medicine)
Abstract Background Understanding the role of space weather, specifically Geomagnetic Disturbances (GMDs) caused by solar activity, on health outcomes is unclear. One emerging link includes the impact of space weather on myocardial infarctions (MI). In this study we examined the correlation between MI and GMDs in Brazil. Methods We used a database from the public health in Brazil, focusing on the city of São José dos Campos (23° 10′ 44″ S, 45° 53′ 13″ W), located in the state of São Paulo, during the period of 1998–2005. We focused on admissions for MIs, which included a total of 871 men and 469 women. We categorized the MI data into three age groups: age 30 and younger, age 31–60, and age over 60. Additionally, we incorporated Planetary Index (Kp) data as an indicator of variations in the Earth’s geomagnetic field resulting from solar disturbances, categorized as quiet, moderate, or disturbed days. In our analysis, we employed two methods: statistical counting and the unsupervised clustering known as K-Means, considering the attributes of age, sex, and geomagnetic condition. Results Here we show that geomagnetic conditions have an impact on MI cases, particularly for women. The rate of relative frequency of MI cases during disturbed geomagnetic conditions is almost three times greater compared to quiet geomagnetic conditions. Using the unsupervised K-Means algorithm, the results indicate that the group associated with disturbed geomagnetic conditions has a higher incidence of MIs in women. Conclusions Overall, our results provide evidence that women may exhibit a higher susceptibility to the effects of geomagnetic disturbances caused by solar activity on MI.